2021
DOI: 10.3390/min11020149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe(III) Oxide Mineralogy and Phosphate on Fe(II) Secondary Mineral Formation during Microbial Iron Reduction

Abstract: The bioreduction of Fe(III) oxides by dissimilatory iron-reducing bacteria may result in the formation of a suite of Fe(II)-bearing secondary minerals, including magnetite (a mixed Fe(II)/Fe(III) oxide), siderite (Fe(II) carbonate), vivianite (Fe(II) phosphate), chukanovite (ferrous hydroxy carbonate), and green rusts (mixed Fe(II)/Fe(III) hydroxides). In an effort to better understand the factors controlling the formation of specific Fe(II)-bearing secondary minerals, we examined the effects of Fe(III) oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 167 publications
(358 reference statements)
1
22
2
Order By: Relevance
“…The presence of phosphate can have pronounced effects on the formation and types of Fe minerals and thus on the rate of microbial Fe‐reduction (O’Loughlin et al., 2021). As organic matter is remineralized, phosphate is released into adjacent pore waters and diffuses upward where it may be released to bottom waters or is sequestered via sorption on primary and secondary Fe‐oxide minerals (e.g., Paytan & McLaughlin, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of phosphate can have pronounced effects on the formation and types of Fe minerals and thus on the rate of microbial Fe‐reduction (O’Loughlin et al., 2021). As organic matter is remineralized, phosphate is released into adjacent pore waters and diffuses upward where it may be released to bottom waters or is sequestered via sorption on primary and secondary Fe‐oxide minerals (e.g., Paytan & McLaughlin, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…O'Loughlin et al found that magnetite formed exclusively when the phosphate concentration was less than 1 mM after ferrihydrite reduction by DIRB. 41 In addition, the SEM characterization of solid products (Fig. 3) revealed the formation of flake crystals on the surface of solid products, which is the typical morphology of vivianite.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 2 shows quantification of total iron (Fe 2+ and Fe 3+ ) in the modified Postgate C medium in the presence of the IRB and carbon steel specimen. As suggested, the concentration of iron increased over time in the presence of the IRB, form 2.2 mg/L after 72 h to 21 mg/L after 168 h. The IRB is known to reduce insoluble Fe(III) oxides such as goethite, hematite, ferrihydrite, akaganéite, and lepidocrocite into soluble ferrous complexes [12,21,35] and this is the most likely reason for the much higher dissolved iron concentration in biotic solution containing IRB. Dissolved sulfide ions were not detected in the solution in the B7 or Postgate C medium containing IRB when tested spectrometrically, using the CuSO 4 technique.…”
Section: Iron and Sulfide Measurements In Solutionmentioning
confidence: 90%